The Effect of Wrestling Tournament on Immune and Endocrine Markers in Blood and Saliva of Male and Female Athletes - Elżbieta Hübner-Woźniak; Teresa Trochimiak (Central European Journal of Sport Sciences and Medicine, 2014)
The aim of the present study was to determine the effect of one-day wrestling tournament on magnitude and direction of changes in selected immunological and endocrine status indices. The participants of the study were male (n = 12) and female (n = 13) wrestlers. The earlobe blood samples and unstimulated saliva were collected at three time points: in the morning before the competition (1), immediately after the last match (2) and in the next morning (3). Total protein, IgA and cortisol concentration and α-amylase activity in saliva, as well as concentration of cortisol and interleukin-6 in serum were measured. Significantly lower ratio of sIgA/protein and significantly higher levels of salivary and serum cortisol, interleukin-6, and α-amylase activity were observed at the second time point compared with the first and the third in both groups of athletes. Regardless of the examined time point, concentrations of serum and saliva markers were similar in female and male wrestlers. However, a tendency to lower sAA activity on the next morning after the tournament compared to basal activity of this enzyme was seen in both examined groups. In general, the changes of examined markers were short-lived, except for α-amylase activity, showing that tournament-wrestling matches had no sustained negative effects on endocrine and immunological body systems.